The determination of copeptin levels helps management decisions among transient ischaemic attack patients. (16th October 2015) - Purroy, F.; Suárez‐Luis, I.; Cambray, S.; Farré, J.; Benabdelhak, I.; Mauri‐Capdevila, G.; Sanahuja, J.; Quílez, A.; Begué, R.; Gil, M. I.; Molina‐Seguin, J.; Torreguitart, N.
Abstract : Background: Most approaches to transient ischaemic attack (TIA) triage use clinical scores and vascular imaging; however, some biomarkers have been suggested to improve the prognosis of TIA patients. Methods: Serum levels of copeptin, adiponectin, neopterin, neuron‐specific enolase, high‐sensitivity C‐reactive protein, IL‐6, N‐terminal pro‐B‐type natriuretic peptide, S100β, tumour necrosis factor‐alpha and IL‐1 α as well as clinical characteristics were assessed on consecutive TIA patients during the first 24 h of the onset of symptoms. Results: Among 237 consecutive TIA patients, 12 patients (5%) had a stroke within 7 days and 15 (6%) within 90 days. Among all candidate biomarkers analysed, only copeptin was significantly increased in patients with stroke recurrence (SR) within 7 days ( P = 0.026) but not within 90 days. A cut‐off point of 13.8 pmol/l was established with a great predictive negative value (97.4%). Large artery atherosclerosis (LAA) [hazard ratio (HR) 12.7, 95% CI 3.2–50.1, P < 0.001] and copeptin levels ≥13.8 pmol/l (HR 3.9, 95% CI 1.01–14.4, P = 0.039) were independent predictors of SR at the 7‐day follow‐up. LAA was the only predictor of 90‐day SR (HR 7.4, 95% CI 2.5–21.6, P < 0.001). ABCD3I was associated with 7‐ and 90‐day SRs ( P = 0.025 and P = 0.034, respectively). The association between copeptin levels and LAA had a diagnostic accuracy of 90.3%. Conclusions: Serum copeptin could be an important prognostic biomarker to guide management decisions among TIA patients. Therefore, TIA patients with copeptin levels below 13.8 pmol/l and without LAA have an insignificant risk of 7‐day SR and could be managed on an outpatient basis.